Pediatric scrub typhus complicated by meningitis - Ya-Ling Chou (Wolters Kluwer Medknow Publications, 2021)
Scrub typhus is caused by the intracellular pathogen Orientia tsutsugamushi, which is transmitted to humans by infected chigger mites. The disease causes a febrile illness accompanied by regional or generalized lymphadenopathy, hepatomegaly, splenomegaly, as well as nonspecific manifestations. Scrub typhus is an important cause of febrile disease in South and East Asia and in the Western Pacific, and can cause severe complications including meningoencephalitis and pneumonitis. Herein, we report a case of scrub typhus accompanied by meningitis, which was definitively diagnosed by serology assay, in a 4-year-old girl who presented with prolonged fever, skin rash, cough, general weakness, and poor appetite. Scrub typhus should be considered in the differential diagnosis when evaluating patients who present with nonspecific febrile illness or meningitis in areas that are endemic for O. tsutsugamushi.